Production Control Study Advocated for Petroleum Division - Earl Oliver (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
IN times like these, the A. I. M. E. and similar societies have their greatest usefulness. . . . Individuals and companies acting alone in the development of public opinion are merely voices crying in the wilderness. United and organized they make a great force that can and does influence public action. . . . What part, if any, then, shall the A. I. M. E. take in these great stabilization processes of civilization? Shall it help to give direction and force to scientific knowledge which comes within its field of activity or shall it merely develop more of it? . . . Is it the A. I. M. E.'s function to help bring system, order and direction out of this situation so that the world can again have forward economic movement, or should it rest on its oars until other agenciess develop that public understanding and direction so necessary for economic progress? As we understand the functions of the A. I. M. E. Petro¬leum Division, they are to discover and promote knowl¬edge for the benefit of society on the mining of oil and gas. To the individual member of the Petroleum Division, there are certain advantages of social and professional contacts, but the collective purpose is that described. And the individual is benefited by membership only as the Division measures up to the purposes of its existence. Consequently, the welfare of this Division and that of its members depends on the extent to which it keeps pace with the needs of society on matters relating to the mining of oil and gas.